2012
DOI: 10.1063/1.4730614
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of solution-processed hydrogenated amorphous silicon single-junction solar cells

Abstract: Hydrogenated amorphous silicon solar cells were fabricated using solution-based processes. All silicon layers of the p-i-n junction were stacked by a spin-cast method using doped and non-doped polydihydrosilane solutions. Further, a hydrogen-radical treatment under vacuum conditions was employed to reduce spin density in the silicon films. Following this treatment, the electric properties of the silicon films were improved, and the power conversion efficiency of the solar cells was also increased from 0.01% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 11 publications
1
58
1
Order By: Relevance
“…Polysilanes can potentially be applied as p-type semiconductors in organic thin film solar cells, but few studies on polysilane solar cells have been reported [1] [8] [9] [10]. Doped polysilanes can act as n-type semiconductors, and while they have been applied in organic solar cells, further investigation is needed [11] [12]. Herein, polysilane thin films were spin-coated from solutions of poly-methylphenyl-silane (PMPS), dimethyl-polysilane (DMPS) and deca-phenyl-penta-silane (DPPS) with phosphorus (P).…”
Section: Introductionmentioning
confidence: 99%
“…Polysilanes can potentially be applied as p-type semiconductors in organic thin film solar cells, but few studies on polysilane solar cells have been reported [1] [8] [9] [10]. Doped polysilanes can act as n-type semiconductors, and while they have been applied in organic solar cells, further investigation is needed [11] [12]. Herein, polysilane thin films were spin-coated from solutions of poly-methylphenyl-silane (PMPS), dimethyl-polysilane (DMPS) and deca-phenyl-penta-silane (DPPS) with phosphorus (P).…”
Section: Introductionmentioning
confidence: 99%
“…The specific resistivity of the Si films prepared from the liquid-Si ink could easily be reduced by hydrogen radical treatment to reduce dangling bonds. 27 The poly-Si film that was produced after annealing at 800 • C greatly improved upon the specific resistivity of the a-Si film as low as 2.0 × 10 3 Ω · cm. The specific resistivity of the nanoimprinted poly-Si pattern was 7.0 × 10 3 Ω · cm, which approaches that of a flat poly-Si film.…”
mentioning
confidence: 99%
“…A following excimer laser irradiation can transform the amorphous silicon (a-Si) film into polycrystalline silicon (poly-Si), a common method for silicon crystallization. Using this silicon ink, a-Si solar cells have been created, 11 as well as poly-Si thin-film transistors (TFTs) with mobilities that were more than 100 times higher than TFTs made from organic and metal-oxide inks. [10][11][12][13] By essentially using silicon as the base material, other advantages arise such as stability, knowledge of the material, and low-power consumption by being able to create complementary metal-oxide semiconductor (CMOS) circuitry, which is often a challenge with the other ink materials.…”
mentioning
confidence: 99%
“…Using this silicon ink, a-Si solar cells have been created, 11 as well as poly-Si thin-film transistors (TFTs) with mobilities that were more than 100 times higher than TFTs made from organic and metal-oxide inks. [10][11][12][13] By essentially using silicon as the base material, other advantages arise such as stability, knowledge of the material, and low-power consumption by being able to create complementary metal-oxide semiconductor (CMOS) circuitry, which is often a challenge with the other ink materials. This silicon ink requires an annealing temperature of at least 350 C in order for the polysilane gel to cross-link sufficiently, 14 which is too high to be used on low-cost flexible substrates that have a low thermal budget such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN) or paper.…”
mentioning
confidence: 99%